2020
DOI: 10.1016/j.jevs.2020.102924
|View full text |Cite
|
Sign up to set email alerts
|

A Farrier Making Every Contact Count: A Microlevel Analysis of Farrier-Client Interaction for Partnership Working in Managing a Horse With Laminitis

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Studies in India ( 37 ) and the United Kingdom demonstrated that long-term (2-year) participatory intervention projects involving animal owners, professionals, and handlers were successful in reducing limb problems and lameness in working horses, promoting adherence to treatment/care plans and positively impacting the quality of human-horse interaction. This style of intervention avoids confrontation and supports clients through a joint exploration of their beliefs, attitudes, and goals as a basis for supporting change in behavior ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in India ( 37 ) and the United Kingdom demonstrated that long-term (2-year) participatory intervention projects involving animal owners, professionals, and handlers were successful in reducing limb problems and lameness in working horses, promoting adherence to treatment/care plans and positively impacting the quality of human-horse interaction. This style of intervention avoids confrontation and supports clients through a joint exploration of their beliefs, attitudes, and goals as a basis for supporting change in behavior ( 40 ).…”
Section: Discussionmentioning
confidence: 99%